The Meaning of the Word "Commission" in the Perspective of Combating Corruption in Indonesia - Zalzulifa, Zalzulifa; Hayati, Asfitri; Dwi Respati, Rella; Utami, Sri (Journal of World Science, 2023)
This study aimed to find out and analyze the meaning of the word commission in a Hizbul Wathan Banten Scout community. This research was conducted using a qualitative descriptive approach, with the target of the Hizbul Wathan scouting movement community in Tangerang, Banten. The data shows that using the word commission is well accepted in a business context, with the number of respondents who disagree as many as three people. While in political and bureaucratic activities, 35 people agreed, and eight said they did not agree. There appears to be vigorous resistance to activities related to social organizations; as many as 13 respondents agreed, and 30 people stated they did not agree. For educational activities, there is a balanced attitude between agreeing and disagreeing. This is evident from the slight difference where as many as 20 respondents agreed. In comparison, 23 respondents stated that they disagreed. The attitude of high rejection was seen in religious activities, with the number of respondents who refused as many as 39 people. Respondents' positive attitude towards using the word commission is generally based on the pragmatic fact that the word commission is also used in various countries. Meanwhile, the negative attitude of the respondents emerged due to the spirit of anti-corruption and cynicism towards the behavior of corruptors who appear in public as if they were innocent.